LIM-only protein FHL2 attenuates vascular tissue factor activity, inhibits thrombus formation in mice and FHL2 genetic variation associates with human venous thrombosis - Kroone, Chantal; Vos, Mariska; Rademakers, Timo; Kuijpers, Marijke; Hoogenboezem, Mark; van Buul, Jaap; Heemskerk, Johan W.M.; Ruf, Wolfram; van Hylckama Vlieg, Astrid; Versteeg, Henri H.; Goumans, Marie-José; de Vries, Carlie J.M.; et al. (Haematologica (Roma), 2020)
Bleeding disorders and thrombotic complications are major causes of morbidity and mortality with many cases being unexplained. Thrombus formation involves aberrant expression and activation of tissue factor (TF) in vascular endothelial and smooth muscle cells. Here, we sought to identify factors that modulate gene expression and activity in these vascular cells. The LIM-only protein FHL2 is a scaffolding protein that modulates signal transduction pathways with crucial functions in endothelial and smooth muscle cells. However, the role of FHL2 in TF regulation and thrombosis remains unexplored. Using a murine model of venous thrombosis in mesenteric vessels, we demonstrated that FHL2 deficiency results in exacerbated thrombus formation. Gain- and loss-of-function experiments revealed that represses TF expression in endothelial and smooth muscle cells through inhibition of the transcription factors nuclear factor κB and activating protein-1. Furthermore, we observed that FHL2 interacts with the cytoplasmic tail of TF. In line with our observations, decreases TF activity in endothelial and smooth muscle cells whereas knockdown or deficiency results in enhanced TF activity. Finally, the single nucleotide polymorphism rs4851770 was associated with the risk of venous thrombosis in a large population of venous thrombosis cases and control subjects from 12 studies (INVENT consortium). Altogether, our results highlight functional involvement of FHL2 in TF-mediated coagulation and identify as a novel gene associated with venous thrombosis in humans.